Autistic Tendencies: The Consequences for Our Culture - FITZGERALD, MICHAEL; Griffin, Joe (My University, 2006)
Professor Michael Fitzgeraldtalks withJoe Griffinabout the powerful impact, both positive and negative, of autistic thinking in diverse walks of life.
Keywords: Autism spectrum disorder; Autism; Asperger syndrome; AUTISM; AUTISM SPECTRUM; Adolescent Psychiatry; Autism; Autism; Autism; Autism; Autism; Autism Genetics; Autistic; Autistic Symptoms; CHILD PSYCHIATRY; COMMUNITY PSYCHIATRY; CONSULTATION LIAISON PSYCHIATRY; CONSULTATION-LIAISON PSYCHIATRY; CULTURE; CULTURES; Culture; GENERAL HOSPITAL PSYCHIATRY; High Functioning Autism; LIAISON PSYCHIATRY; Neuropsychiatry; Neuropsychiatry; PSYCHIATRY; Psychiatry; Psychiatry; TRAINEES IN PSYCHIATRY; autistic spectrum disorder; child and adolescent Psychiatry; forensic psychiatry; neurodevelopmental psychiatry